2021
DOI: 10.1002/aenm.202100210
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Interfacial Chemical and Electrochemical Reactions of Sulfide‐Based All‐Solid‐State Batteries

Abstract: The success of ASSLBs could eventually eliminate the mileage anxiety and safety concerns of electric vehicles (EVs). To enable ASSLBs, various solid-state electrolytes have been intensively developed over the past decades, such as sulfide electrolytes (SEs), [1b,c,2] oxide electrolytes, [3] polymer-based electrolytes, [4] and emerging solid-state halide electrolytes (Li 3 MCl 6 , M = Y, In, Er, Sc, etc.). [5] Owing to the high ionic conductivity and soft mechanical properties of SEs, it is widely believed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 50 publications
1
61
0
Order By: Relevance
“…LiCoO 2 , Nirich layered oxides, LRLO, and Li-free cathodes) are enabling the construction of high-energy-dense SSBs [33]. Figure 3 schematically presents their properties in terms of volume change, specific capacity, rate capability, working voltage, cost, and cycle performance (in ascending order of specific capacity) [27,28,[39][40][41][42][43][44]. The upper cutoff voltage of commercial cathode material LiCoO 2 (LCO) was only 4.2 V vs. Li + /Li, which possesses only a specific capacity of 137 mAh g −1 [45].…”
Section: Overview Of High-energy Cathode Materials In Ssbsmentioning
confidence: 99%
“…LiCoO 2 , Nirich layered oxides, LRLO, and Li-free cathodes) are enabling the construction of high-energy-dense SSBs [33]. Figure 3 schematically presents their properties in terms of volume change, specific capacity, rate capability, working voltage, cost, and cycle performance (in ascending order of specific capacity) [27,28,[39][40][41][42][43][44]. The upper cutoff voltage of commercial cathode material LiCoO 2 (LCO) was only 4.2 V vs. Li + /Li, which possesses only a specific capacity of 137 mAh g −1 [45].…”
Section: Overview Of High-energy Cathode Materials In Ssbsmentioning
confidence: 99%
“…Additionally, a few emerging advanced characterization technologies will be discussed that deepen the understanding of the structure-function relationship in 2DMs for ASSLBs. [47][48][49] Finally, future research directions are proposed to accelerate the technology developments, from the fundamental understanding of mechanisms to the improvement of materials and applications.…”
Section: Introductionmentioning
confidence: 99%
“…The highly oxidized transition metal ions and O 2À in CAMs tend to induce and expedite the oxidative decomposition of sulfide SEs, which also makes the composition of CEI more complicated. 104,159 For example, Banerjee et al 145 successfully separated the interfacial chemical reactions from the electrochemical decomposition reactions of SEs and determined the corresponding reaction products at the initial state and the charged state of the cells by decoupling each effect, respectively. They employed XRD, Raman, XPS, and so on, to identify the interphase compositions and found that significant amounts of crystalline LiCl, Li 3 PO 4 , and Ni 3 S 4 were probed at the interfaces under the charged state, while the signals of these components were much weaker at the pristine state.…”
Section: The Electrochemical Reaction Occurs At Interfacesmentioning
confidence: 99%
“…Moreover, the chemical reactions between CAMs and SEs will be exacerbated during electrochemical cycling. The highly oxidized transition metal ions and O 2− in CAMs tend to induce and expedite the oxidative decomposition of sulfide SEs, which also makes the composition of CEI more complicated 104,159 . For example, Banerjee et al 145 successfully separated the interfacial chemical reactions from the electrochemical decomposition reactions of SEs and determined the corresponding reaction products at the initial state and the charged state of the cells by decoupling each effect, respectively.…”
Section: Interfacial Issuesmentioning
confidence: 99%